The Computer in Accounting Education . - Nielsen, Gordon L. (The Accounting Review, 1965)
Abstract The article focuses on the use of computers to show the students how accounting provides the data for a total management information and decision-making system, as well as how it reduces the purely clerical routine formerly associated with accounting. In 1964 American Accounting Association Committee on Courses and Curricula–EDP reported that under graduate accounting students need a three-fold exposure to electronic data processing, concurrent with or prior to the introductory accounting course-basic programming instruction, as an approach to problem-solving in a variety of accounting courses, and as an integral part of the accounting systems course. There are several advantages to be gained from integrating computer programming into the elementary accounting course. These advantages are significant enough to warrant integration at the expense of two or three conventional written assignments, or even in lieu of a chapter or more of certain traditional first-year material. Among the several areas of elementary accounting instruction that are adaptable to computer application, none is more apparent than payroll accounting.